Mudança institucional e fragmentação das centrais sindicais no Brasil - Paula Vivacqua de Souza Galvão Boarin (2021)
The purpose of this thesis is to understand the impact of labor legislation on the fragmentation of union centrals. Based on a qualitative analysis approach, the historical comparative method was used for the longitudinal study of the brazilian case, covering the period between the 1990s and the approval of the Labor Reform of 2017. Part of the legacy of the assembly of corporatism, fragmentation, which has its legal framework in the Consolidation of Labor Laws (CLT), survived the Federal Constitution of 1988. However, the Reform, above all by extinguishing the compulsory union tax, would have opened the possibility of profound alteration of this legacy and, therefore, of the fragmented character of the worker’s organization at the peak. Understanding the relationship between fragmentation and the ability to coordinate political action, which, in turn, affects the degree of material gains for workers, it was relevant to investigate how, between incentives and constraints, the corporatist legacy survived in the re-democratized country, in different political and macroeconomic contexts. With the New Historical Institutionalism as the theoretical lens of analysis, the hypothesis is that changes in the research relationship occur incrementally, and not as a result of critical events. The thesis, in addition to the introductory text and the conclusions, has five chapters. In the first, the theoretical foundations of the research are outlined, as the context of construction of corporatism and the emergence of union centrals. In the second and third chapters, the legislation is analyzed in the light of the political, macroeconomic context and union dynamics under the neoliberal reforms and the governments of the Worker’s Party, respectively. In the fourth chapter, in addition to the general characterization of Labor Reform, aspects that help to think about fragmentation are contrasted, in the last chapter, to explore the hypothesis that such institutional change occurred incrementally. The results point, in addition to the identification of institutional markers of fragmentation in each period of analysis, for the survival of some of these elements to 2017. Thus, if the arrangement moves towards a pluralization, this cannot happen without the complete dissolution of the legacy. This opens up the prospect of considering the fragmentation of union centrals as one of the key elements to understand democratic deficits in the brazilian case and in others to be explored in the future.